A multi-band switchable antenna for Wi-Fi, 3G Advanced, WiMAX, and WLAN wireless applications. Issue 8 (11th May 2018) - Ullah, Sadiq; Ahmad, Shaheen; Khan, Burhan A.; Flint, James A.
Abstract: This paper presents a hexa-band frequency reconfigurable planar antenna, printed on a 1.6 mm thicker FR 4 substrate and backed by a truncated ground plane. The given antenna operates in four different frequency modes, depending on the state of the two lumped element switches. The proposed antenna works at six frequencies, 2.10, 2.40, 3.35, 3.50, 5.28, and 5.97 GHz. These frequency bands are dedicated to useful wireless applications, including 3G Advanced (2.10 GHz), Wireless Fidelity (Wi-Fi) (2.40 GHz), WiMAX (3.35 GHz), WiMAX (3.5 GHz), WLAN (5.28 GHz) and fixed-satellite and mobile satellite services (5.97 GHz). Satisfactory gain of 1.96, 2.20, 2.671, 2.81, 3.80, and 3.88 dBi, efficiency of 92.5, 94.5, 94.56, 95.0, 93.8, and 97.0% and bandwidth of 332, 485, 1020, 1080, 512, and 465 MHz has been obtained at 2.10, 2.40, 3.35, 3.50, 5.28, and 5.97 GHz, respectively. The modeling and simulations are conducted in CST MWS (2014). The simulated reflection coefficient and radiation pattern are validated in antenna measurement facility. In addition, the specific absorption rate of the antenna on a flat section of human body is also studied. The antenna is compact, low profile, and vastly suitable for multi-band wireless devices.